A Handbook on Commerce & Management Applications, Concepts and Technologies (Volume 1) - Rajesh Gupta (AG Volumes, 2021)
The purpose of this article is to provide an overview of how strategic decision-making has changed through time in companies and to make a recommendation for a more holistic approach. It is the goal of this study to contribute to literature on strategy formulation procedures. Inquiries into the precise process aspects of strategy generation are explored in this paper. Additional studies of characteristics of good strategic decision making , grouping of organization as per the different information and the role of information is thoroughly reviewed.